Osteopontin expression and its relationship with prognostic biomarkers in canine mammary carcinomas - Monteiro, Lidianne N.; Salgado, Breno S.; Oliveira, Deilson E. [UNESP]; Rivera-Calderon, Luis G.; Montoya-Flórez, Luis M.; Sanctis, Paula [UNESP]; Rocha, Noeme S. [UNESP] (FapUNIFESP (SciELO), 2020)
Osteopontin is a glycophosphoprotein implicated in different physiologic and pathologic processes and is known to be involved in progression and metastasis of various cancers in humans, but this relation is still little explored in the veterinary. The aim was to evaluate the expression of osteopontin in canine mammary carcinomas and its relation with well-established canine mammary tumor biomarkers. For that, expression of OPN, EGFR, HER2, and c-Kit were evaluated along with Ki67 rate in 43 mammary carcinomas. Osteopontin was demonstrated to be expressed by neoplastic epithelial cells in all carcinomas as well as in stromal cells from the tumor microenvironment. Relation between high osteopontin expression and EGFR positivity (P<0.001) and HER2 overexpression (P=0.012) was demonstrated. In conclusion, high OPN expression seems to be related to poor prognosis and MAPK pathway activation, given the association with EGFR and HER2, members of the MAPK signaling pathway.
Expessão de osteopontina e sua relação com biomarcadores prognóstico nos carcinomas mamários caninos
Keywords: Cancer; Canine mammary carcinomas; Dogs; Epidermal growth factor receptor; Human epidermal growth factor receptor 2; Immunohistochemistry; Osteopontin expression; Prognostic biomarkers